HIV: ageing, cognition and neuroimaging at 4‐year follow‐up. Issue 6 (14th February 2018) - Haynes, BI; Pitkanen, M; Kulasegaram, R; Casey, SJ; Schutte, M; Towgood, K; Peters, B; Barker, GJ; Kopelman, MD
Abstract : Objectives: The aim of the study was to investigate the hypothesis of accelerated cognitive ageing in HIV‐positive individuals using longitudinal assessment of cognitive performance and quantitative magnetic resonance imaging (MRI). Methods: We assessed a broad cognitive battery and quantitative MRI metrics [voxel‐based morphometry (VBM) and diffusion tensor imaging (DTI)] in asymptomatic HIV‐positive men who have sex with men (15 aged 20–40 years and 15 aged ≥ 50 years), and HIV‐seronegative matched controls (nine aged 20–40 years and 16 aged ≥ 50 years). Results: Being HIV positive was associated with greater decreases in executive function and global cognition. Additionally, using DTI, we found that the HIV‐positive group had a greater increase in mean diffusivity, but we did not find group differences in volume change using VBM. With respect to the HIV status by age group interaction, this was statistically significant for change in global cognition, with older HIV‐positive individuals showing greater global cognitive decline, but there were no significant interaction effects on other measures. Lastly, change in cognitive performance was correlated with change in the DTI measures, and this effect was stronger for the HIV‐positive participants. Conclusions: In the present study, we found some evidence for accelerated ageing in HIV‐positive individuals, with a statistically significant HIV status by age group interaction in global cognition, although this interaction could not be explained by the imaging findings. Moreover, we also found that change in cognitive performance was correlated with change in the DTI measures, and this effect was stronger for the HIV‐positive participants. This will need replication in larger studies using a similarly lengthy follow‐up period.